Maqāṣid al-Sharī‘ah Between Classical and Postmodern Periods: an Advanced Islamic Juridical Context - Prof. Dr. Muhammad Munir; Prof. Dr. Muhammad Tayyeb Nadeem (MEI, 2023)
The study of Maqāṣid al-Sharī‘ah or the higher objectives of Islamic law and maṣlaḥah has attracted the attention of eminent scholars since the second-century hijrī. This work discusses what is Maqāṣid and maṣlaḥah? Who were the premodern as well as the postmodern scholars who focused on the Maqāṣid cum maṣlaḥah? Why the premodern jurists did not give a definition of the term, Maqāṣid al-sharī‘ah? What is the nature and structure of the Maqāṣid? What are the types of the Maqāṣid? Are there priorities within the Maqāṣid? Why are the Maqāṣid confined to five only? Can the scope of the Maqāṣid be broadened? What is the reason for expanding the essential five to include many others? The most noticeable works on Maqāṣid cum maṣlaḥah in premodern times is by Imam al-Ḥaramayn al-Juwaynī, Muḥammad al-Ghazālī and Ibrāhīm b. Mūsā al-Shāṭibī. There are many scholars in the 20th and 21st centuries who focused on the maqāṣid. The most important work is by Ṭāhir b. ‘Āshūr. Scholars have focused on maqāṣid cum maṣlaḥah because these are considered as vehicles for change in the legal, social, political, and economic issues. Postmodern scholars have expanded the scope of the Maqāṣid to include, inter alia, justice, freedom, equality, and rights etc.